Management and Outcome of Liver Trauma in Jinnah Hospital Lahore - Sehrish Majeed, Zain Ul Abideen Ali, Tahir Hamid, Amir Usman, Javeria Usman, Fahad Abbas, Mansab Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Liver injury is the most commonly encountered trauma among all abdominal traumas. It is associated with high morbidity and mortality. The choice of treatment for such injury depends on the type as well as severity of injury. Objective: To determine the outcome in terms of (success and complications) of managing liver trauma either conservatively or with operative management. Methodology: 62 patients with liver trauma (blunt or penetrating) who presented in the surgical emergency department of Jinnah Hospital, Lahore were enrolled in the study. Detailed history, clinical examination and radiological examination of all patients were carried out using CT scan. Depending on the grade of injury and type of trauma patients were managed either conservatively or by operating them. Success of treatment and its outcomes were noted down. Results: The results revealed that the mean age of the patients was 40.1±11.74, mean diastolic blood pressure was 62.34±14.36, mean systolic blood pressure was 105.2±11.41, mean pulse rate was 92.37±19.06, mean respiratory rate was 19.8±5.353 and mean number of fresh frozen plasma (FFPs) infused were 2.8±0.81. Conservative management was carried out in 42 (67.7%) patients and operative management was carried out in 20 (32.3%). Out of these, conservative management was successful in 35 (56.5%) patients and operative management was successful in 18 (29%) patients. Common complications seen were intra-abdominal sepsis in 24.2%, bile leakage 14.5%, recurrent hemorrhage 6.5%, coagulopathy 3.2% and death 4.8%. Conclusion: Conservative management of liver trauma is highly successful and is associated with less complications and unless needed must be adapted and operative management should only be carried out in patients who have injury to liver of such an extent that cannot be managed conservatively.